Engineered mRNA-expressed antibodies prevent respiratory syncytial virus infection - Pooja Munnilal Tiwari (Nature Portfolio, 2018)
Engineered neutralizing antibodies are potential therapeutics for numerous viruses, such as respiratory syncytial virus (RSV). Here, the authors develop an mRNA-based approach to express membrane-anchored neutralizing antibodies in the lung and demonstrate that it inhibits RSV infections in mice.